Parametric and semiparametric estimation and testing of age effects in selection models: The Philippine case - Dacuycuy, Lawrence B. (Animo Repository, 2021)
In this paper, the adequacy of the usual parametric selection models evaluated in terms of the validity of the assumed link and index functional specifications is investigated using non-parametric-based test procedures. Utilizing the said procedures, the study verifies whether the specifications of age in sectoral participation equations is linear, instead of the usual practice of automatically resorting to the quadratic functional form. Using the 1998 Annual poverty indicators survey, the study finds that at higher levels of bandwidth, the logit link appears to be more valid relative to the probit link, a key result that requires a careful assessment